Estudos do Mecanismo de Catálise da Pirofosforilase UDP-N-acetilglucosamina do Moniliophthora perniciosa por Métodos QM/MM - Teles, André L. B.; dos Santos Júnior, Manoelito Coelho; Braga, Vanildo Martins Lima; Taranto, Alex Gutterres (Orbital: The Electronic Journal of Chemistry, 2015)
The fungus Moniliophthora perniciosa is the causal agent of the witches’ broom disease of cacao (Theobroma cacao). This fungus has a pyrophosphorylase enzyme to catalyze the formation of UDP-N-acetylglucosamine-1-phosphate, an intermediate  in the biosynthesis of the fungal cell wall. This enzyme was studied by QM/MM methods to understand its catalytic mechanism. Initially, the structure was refined and submitted to molecular dynamics simulations. Next, QM/MM calculations were used to scan the coordinates of the reaction from the reactants to products; an SN2 mechanism has been proposed of the aforementioned reaction. In this system, the nucleophile is the oxygen atom of the phosphate group from N-acetylglucosamine-1-phosphate. It attacks the phosphorus of the alfa-phosphate from the uridine triphosphate to form UDP-N-acetylglucosamine and pyrophosphate. The calculated reaction was exothermic (ΔH = -81.01 Kcal/mol). On the reaction pathway, the most energetic structure had the phosphorus atom attacked in a pentacoordinate configuration. This structure interacts with the catalytic site composed by the residues Gly112, Gly113, Arg116, Lys123 and Gly225 through hydrogen bonds. During the mechanism study, the geometry of the transition state was obtained. Thus, the generation of new compounds sharing a geometric similarity with this pentacoordinate transition state can lead to the development of more active compounds possessing antifungal proprieties against witch's broom.DOI: http://dx.doi.org/10.17807/orbital.v7i3.629